Functional gastrointestinal disorders in infants which reflect the disorders in the relationships in mother–child dyad - M. I. Dubrovskaya; E. I. Gryaznovaw (Лечащий Врач, 2021)
The article discusses the functional disorders of the gastrointestinal tract in infants. The types of psychological component of gestational dominant are described. Modern data on psychogenic disorders and eating behavior are presented: regurgitation, bulimia, refusal to eat, which reflect inadequate interaction of the mother with the child. Colic, crying and anxiety of the child are associated with depression and anxiety of the mother.